Ethical and Policy Implications of Financial Burden in Family Caregivers. Issue 5 (6th October 2022) - Thomas Hebdon, Megan C.; Phan, Cuong T.; Phillips, Carolyn; Wan, Shaowei; Doyon, Katherine; Gray, Tamryn; Johnson, Lee; Fischer, Stacy M.
Abstract : Palliative care nurses are key members of the health care team and provide support to patients and their families navigating chronic and life-limiting illness. Financial burden is an issue inherent to chronic illness, yet has not been fully addressed in family caregivers. The purpose of this article is to (1) provide a case study of a family caregiver navigating chronic illness with her daughter and the associated financial and employment consequences and (2) review the nursing ethical, policy, and practice implications of financial burden for family caregivers. The ethical implications of financial burden in family caregivers relate to health equity and health outcomes for both the patient and family caregiver in treatment access and quality. The policy implications include state and federal policies related to caregiver compensation and support and family medical leave. Palliative care nurses play an integral role in addressing caregiver financial burden through assessment, education, referral, and policy support. Family caregivers are essential to the palliative care team, and palliative care nurses have the opportunity to lead initiatives to support the financial well-being of family caregivers in practice, research, and policy settings.